Gata3ZsG and Gata3ZsG-fl: Novel murine Gata3 reporter alleles for identifying and studying Th2 cells and ILC2s in vivo - Gurram, Rama K.; Wei, Danping; Yu, Qiao; Kamenyeva, Olena; Chung, Hyunwoo; Zheng, Mingzhu; Butcher, Matthew J.; Kabat, Juraj; Liu, Chengyu; Khillan, Jaspal S.; Zhu, Jinfang (Frontiers in Immunology, 2022)
T helper-2 (Th2) cells and type 2 innate lymphoid cells (ILC2s) play crucial roles during type 2 immune responses; the transcription factor GATA3 is essential for the differentiation and functions of these cell types. It has been demonstrated that GATA3 is critical for maintaining Th2 and ILC2 phenotype in vitro; GATA3 not only positively regulates type 2 lymphocyte-associated genes, it also negatively regulates many genes associated with other lineages. However, such functions cannot be easily verified in vivo because the expression of the markers for identifying Th2 and ILC2s depends on GATA3. Thus, whether Th2 cells and ILC2s disappear after Gata3 deletion or these Gata3-deleted “Th2 cells” or “ILC2s” acquire an alternative lineage fate is unknown. In this study, we generated novel GATA3 reporter mouse strains carrying the Gata3ZsG or Gata3ZsG-fl allele. This was achieved by inserting a ZsGreen-T2A cassette at the translation initiation site of either the wild type Gata3 allele or the modified Gata3 allele which carries two loxP sites flanking the exon 4. ZsGreen faithfully reflected the endogenous GATA3 protein expression in Th2 cells and ILC2s both in vitro and in vivo. These reporter mice also allowed us to visualize Th2 cells and ILC2s in vivo. An inducible Gata3 deletion system was created by crossing Gata3ZsG-fl/fl mice with a tamoxifen-inducible Cre. Continuous expression of ZsGreen even after the Gata3 exon 4 deletion was noted, which allows us to isolate and monitor GATA3-deficient “Th2” cells and “ILC2s” during in vivo immune responses. Our results not only indicated that functional GATA3 is dispensable for regulating its own expression in mature type 2 lymphocytes, but also revealed that GATA3-deficient “ILC2s” might be much more stable in vivo than in vitro. Overall, the generation of these novel GATA3 reporters will provide valuable research tools to the scientific community in investigating type 2 immune responses in vivo.